Are phosphodiesterase type 5 inhibitors associated with increased risk of melanoma?: A systematic review and meta-analysis. Issue 3 (January 2018) - Feng, Shijian; Zhou, Liang; Liu, Qinyu; He, Qing; Liao, Banghua; Wei, Xin; Li, Hong; Wang, Kunjie; Zhu, Yuchun
Abstract : Abstract: Phosphodiesterase type 5 (PDE5) inhibitors are recommended for patients with erectile dysfunction by American Urological Association and European Association Urology guidelines. However, recent researches have shown that PDE5 inhibitors may lead to increased melanoma risk. Thus, we aimed to explore whether PDE5 inhibitors are associated with increased melanoma risk based on published literatures. We conducted a systematic online search on PubMed, EMBASE, Cochrane Library, Chinese Biochemical Literature, China National Knowledge Infrastructure, and Chinese Science and Technology Periodical databases to identify the related studies. Odds ratios (ORs), risk ratios, and hazard ratios with 95% confidence intervals (CIs) were extracted and calculated to assess the strength of associations between PDE5 inhibitors and melanoma risk. We also extracted the basal cell carcinoma (BCC) to validate the association in this study. We included 5 studies containing 100, 932 participants in our systematic review and meta-analysis. The calculated results suggested positive results of PDE5 inhibitors on melanoma risk (OR: 1.13; 95%CI: 1.04–1.23). For localized and nonlocalized melanoma, the results were different (OR: 1.22; 95%CI: 1.04–1.43 for localized melanoma) (OR: 0.62; 95%CI: 0.39–0.98 for nonlocalized melanoma). It also showed that PDE5 inhibitors were associated with increased BCC risk (OR: 1.18; 95%CI: 1.11–1.27). The association between PDE5 inhibitors and melanoma might not be causal due to potential bias (patient selection, and so on) and limitations.